Temporal neuronal differentiation programs safeguard neuronal diversity - Dan Shen; Jingyi Chu; Xiaolin Zhou; Zejun Lan; Rulan Zhang; Shuyu Wang; Haoxuan Tang; Yunrui Wang; Chenlei Hu; Zhiyuan Li; Yan Song (Proceedings of the National Academy of Sciences, 2026)
Differentiation programs actively lock neurons into a terminally differentiated state. How differentiation programs operate in distinct neuronal lineages remains obscure. Here, we found that previously well-characterized Drosophila neuronal differentiation factors are specifically expressed in the central brain late-born neurons but not early-born neurons, indicating the existence of a distinct, early differentiation program. We next identified T cell factor (TCF) and Odd-paired (Opa)/Zic as part of the early differentiation program that is specifically expressed in the early-born neurons to prevent neuronal dedifferentiation, partly through restricting Chinmo expression. At the molecular level, TCF promotes neuronal differentiation through a Wnt-independent noncanonical mode, via forming a transcriptional complex with Opa. Together, our study unveils that distinct differentiation programs operate in fly central brain early-born versus late-born neurons. Such customized differentiation mechanism whereby temporal differentiation programs safeguard their corresponding temporal identity specification programs is likely to also operate in mammalian brain development.